Bioelectricity Production from Various Feedstocks Using Pure Strain of Bacillus firmus - Shweta Singh; Anjana Pandey; Chandra Kant Dwivedi (Center of Biomass & Renewable Energy, Diponegoro University, 2016)
Microbial fuel cells (MFCs) are bio-electrochemical devices that exploit microorganisms for producing electricity from a variety of materials, including complex organic waste and renewable biomass. In this study, the heterotrophic microbe, Bacillus firmus was used as the active bacterial component with synthetic waste waters for bio-electricity production. Three identical mediatorless and membraneless single chambered microbial fuel cells (MFCs) without catalyst was fabricated with different carbon source and operated in batch mode. The performance of these MFCs with glucose, hydrolyzed potato peel and hydrolyzed cyanobacterial biomass substrates were comparatively evaluated. Among these substrates hydrolyzed cyanobacterial biomass was found to be the favorable substrate for electricity production whereas potato peel was unable to construct a well-established MFC. The maximum power density of 16.46mW/m2 at 62.48mA/m2 was achieved using cyanobacterial mass as the substrate. A current density of 53.47mA/m2 appeared to characterize the maximum power produced from a polarization test was 5.85mW/m2 for glucose substrate. Article History: Received February 25th 2016; Received in revised form April 18th 2016; Accepted May 19th 2016; Available onlineHow to Cite This Article: Singh, S., Pandey, A. and Dwivedi, C.K. (2016) Bioelectricity Production from Various Feedstocks Using Pure Strain of Bacillus firmus. Int. Journal of Renewable Energy Development, 5(2), 119-127.http://dx.doi.org/10.14710/ijred.5.2.119-127